Assessment of the effect of complete dentures on respiratory performance: A spirometric analysis - Jawaz Ahmad Shah Bukhari; Sidhant Sudan; Bhushan Bangar; Neeraj Kumar; Prateek Bhatia; Rohit Duggal (Wolters Kluwer Medknow Publications, 2021)
Background: Among the vital functions, respiration can be claimed to be one of the most important. A thorough understanding of the patient should be an important aspect a prosthodontist should dwell into so as to predispose patients to acknowledge the kind of prosthesis they require. Hence, the present study was conducted for assessing the effect of complete dentures on respiratory performance. Materials and Methods: Fifty patients with the presence of complete edentulous arch and who had a history of complete denture usage for at least 5 years were enrolled. All the spirometric procedures were performed by trained technicians. A diagnostic spirometer was employed for performing the spirometric test. Testing was carried out in the following steps: Stage 1: testing in the absence of denture, Stage 2: testing in the presence of both dentures, Stage 3: testing in the presence of maxillary denture only, and Stage 4: testing in the presence of mandibular dentures only. Forced vital capacity (FVC) value, peak expiratory flow (PEF) value, forced expiratory volume in 1 s (FEV1) value, and forced expiratory flow 25%-75% (FEF25-75) value were recorded with the spirometric test. Analysis of all the results was done by SPSS software. Results: The spirometric value of FVC, PEF, FEV1, and FEF25-75 in the absence of both maxillary and mandibular dentures (Stage 1) was found to be 3.18, 5.83, 2.44, and 2.80, respectively. The spirometric value of FVC, PEF, FEV1, and FEF25-75 in the presence of both maxillary and mandibular dentures (Stage 2) was found to be 3.09, 5.67, 2.41, and 2.67, respectively. While analyzing statistically, it was seen that there was a significant decrease in the value of spirometric variables in the presence of dentures. Conclusion: Chronic denture wearer edentulous patients are subjected to the risk of development of spirometric alterations. Hence, these patients should be given timely instructions about the various respiratory exercise protocols.